Accelerating access and scale-up of optimized ART in low-income and middle-income countries: a call for a coordinated end-to-end approach. Issue 4 (July 2017) - Harris, Emily; Pérez-Casas, Carmen; Barnhart, Matthew; Lin, Amy H.; Ferris, Danielle; Ajose, Olawale; Burgess, Emma K.; Fowler, Rachel
Abstract : Purpose of review: To discuss how aligning the collective power of scientists, regulators, drug companies, donors, implementers and advocates to achieve a single goal – accelerating access to simpler, safer, more robust and more affordable HIV treatment – can rapidly advance antiretroviral optimization efforts and enable scale-up. Recent findings: Harmonization of traditionally sequential processes can address the delays commonly experienced in introducing new products to low-income and middle-income countries, by facilitating an 'end-to-end' approach that mitigates risk and encourages early planning for all aspects of product introduction. Summary: Planning with the 'end-in-mind' can facilitate healthy markets, benefit the application of new technologies, and accelerate the development of improved products in parallel (versus traditionally sequential efforts).